(untitled) (Academic Journal of Internal Affairs, 2018)
In this study I have summarized the main elements of cyber protection in Hungary, highlighting the most important strategy, legal rules and organizations. After that I have also presented the service provider – user model emerging due to the consolidation of info-communication systems at state and self-governments and its effect on cyber-protection. In this context I have shown that the present legal rules are not able to handle task and responsibility limitations resulting hereby. I have presented that the appointed central service provider in Hungary, the NISZ Zrt., can fulfil its obligations prescribed in law regulations mentioned above, that it can provide cloud-based services and therefore I have summarized characteristics and grouping of cloud-based systems. I have also presented which of them are recommended for state institutions by big international organizations and in which one NISZ Zrt. provides services.